NCRP Report no.180—management of exposure to ionizing radiation: NCRP radiation protection guidance for the United States. (28th August 2019) - Cool, D A; Kase, K R; Boice, J D
Abstract: NCRP Report No. 180, 'Management of Exposure to Ionizing Radiation: Radiation Protection Guidance for the United States (2018)' was developed by Council Committee 1. The report builds and expands upon previous recommendations of NCRP and ICRP, covering exposure to radiation and radioactive materials for five exposure categories: occupational, public, medical, emergency workers, and nonhuman biota. Actions to add, increase, reduce or remove a source of exposure to humans require justification. Optimisation of protection universally applies, taking into account societal, economic, and environmental factors; addressing all hazards, and striving for continuous improvement when it is reasonable to do so. Numeric protection criteria for management of dose to an individual for a given exposure situation are provided, and differ in some respects from ICRP. A specific numeric criterion is suitable to be designated as a regulatory dose limit only when the source of exposure is stable, characterised, and the responsible organisation has established an appropriate radiation control program in advance of source introduction. Medical exposure includes patients, comforters and caregivers of a patient, and voluntary participants in biomedical research. Emergency workers are a new exposure category; their exposure is treated separately from occupational, public or medical exposure, and numeric criteria are provided for deterministic and stochastic effects. For nonhuman biota, the focus is on population maintenance of the affected species, and a guideline is provided for when additional assessment may be necessary. In addition, the recommendations emphasise that: ethical principles support decision-making; stakeholder engagement is necessary in deciding suitable management of their radiation exposure; and a strong safety culture is intrinsic to effective radiation protection programs.